Subclinical Vascular Disease in Children With Human Immunodeficiency Virus in Uganda Is Associated With Intestinal Barrier Dysfunction. (6th December 2019) - Dirajlal-Fargo, Sahera; Albar, Zainab; Bowman, Emily; Labbato, Danielle; Sattar, Abdus; Karungi, Christine; Longenecker, Chris T; Nazzinda, Rashida; Funderburg, Nicholas; Kityo, Cissy; Musiime, Victor; McComsey, Grace A
Abstract: Background: The risk of cardiovascular disease (CVD) and its mechanisms in children living with perinatally acquired HIV (PHIV) in sub-Saharan Africa has been understudied. Methods: Mean common carotid artery intima-media thickness (IMT) and pulse-wave velocity (PWV) were evaluated in 101 PHIV and 96 HIV-negative (HIV−) children. PHIV were on ART, with HIV-1 RNA levels ≤400 copies/mL. We measured plasma and cellular markers of monocyte activation, T-cell activation, oxidized lipids, and gut integrity. Results: Overall median (interquartile range, Q1–Q3) age was 13 (11–15) years and 52% were females. Groups were similar by age, sex, and BMI. Median ART duration was 10 (8–11) years. PHIV had higher waist–hip ratio, triglycerides, and insulin resistance ( P ≤ .03). Median IMT was slightly thicker in PHIVs than HIV− children (1.05 vs 1.02 mm for mean IMT and 1.25 vs 1.21 mm for max IMT; P < .05), while PWV did not differ between groups ( P = .06). In univariate analyses, lower BMI and oxidized LDL, and higher waist–hip ratio, hsCRP, and zonulin correlated with thicker IMT in PHIV ( P ≤ .05). After adjustment for age, BMI, sex, CD4 cell count, triglycerides, and separately adding sCD163, sCD14, and hsCRP, higher levels of intestinal permeability as measured by zonulin remained associated with IMT (β = 0.03 and 0.02, respectively; P ≤ .03). Conclusions: Our study shows that African PHIV have evidence of CVD risk and structural vascular changes despite viral suppression. Intestinal intestinal barrier dysfunction may be involved in the pathogenesis of subclinical vascular disease in this population. Abstract : Children with perinatally acquired HIV (PHIV) in Uganda have evidence of cardiovascular disease risk and structural vascular changes despite viral suppression with antiretroviral therapy. Intestinal barrier dysfunction may be involved in the pathogenesis of subclinical vascular disease in this population.